Nontyphoidal Salmonella septic arthritis in an elderly man: A case report - Dongjie Yu; Linlin Sun (IDCases, 2025)
Nontyphoidal Salmonella septic arthritis is an uncommon complication of NTS bacteremia in adults. A 75-year-old patient was admitted for right hip pain, presenting with manifestations of septic shock. Following a series of examinations, the patient was diagnosed with nontyphoidal Salmonella septic hip arthritis. Treatment included antibiotics, debridement, and the implantation of a spacer. The patient recovered and was able to ambulate slowly with a cane. The patient ultimately opted for continued oral antibiotic therapy to avoid infection recurrence, rather than undergoing a two-stage total hip replacement, after achieving satisfactory activities of daily life.